2019
DOI: 10.1111/ijcp.13444
|View full text |Cite
|
Sign up to set email alerts
|

Risk stratification in acute coronary syndrome: Evaluation of the GRACE and CRUSADE scores in the setting of a tertiary care centre

Abstract: Objective Risk assessment plays a decisive role in the management of acute coronary syndrome (ACS). The GRACE and the CRUSADE scores are among the most frequently used risk assessment tools.
We aimed to compare the performance of the GRACE and CRUSADE risk scores to predict in‐hospital mortality and major bleeding in a contemporary ACS population at a high‐volume academic hospital. Methods All patients treated for ACS from January 1, 2006 to December 31, 2015 at a tertiary care centre were prospectively enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 19 publications
1
11
0
1
Order By: Relevance
“…Our result was similar to Tscherny et al (2019), which reported the median Troponin I value of 9 ng/mL and CKMB of 53 U/L. [12] The mean cholesterol level in the study was 172.65 mg/dl, LDL 125.02 mg/dl, HDL 33.29 mg/dl, and triglyceride 134.47 mg/dl. Other studies also reported lipid profile results in ACS patients, in which the mean total cholesterol was 4.96 mmol/L, LDL 3.18 mmol/L, triglyceride 1.3 mmol/L, and HDL 1.16 mmol/L.…”
Section: Discussionsupporting
confidence: 91%
“…Our result was similar to Tscherny et al (2019), which reported the median Troponin I value of 9 ng/mL and CKMB of 53 U/L. [12] The mean cholesterol level in the study was 172.65 mg/dl, LDL 125.02 mg/dl, HDL 33.29 mg/dl, and triglyceride 134.47 mg/dl. Other studies also reported lipid profile results in ACS patients, in which the mean total cholesterol was 4.96 mmol/L, LDL 3.18 mmol/L, triglyceride 1.3 mmol/L, and HDL 1.16 mmol/L.…”
Section: Discussionsupporting
confidence: 91%
“…According to the degree of luminal narrowing, severity scores reflecting angiographic stenosis of the coronary artery segment were 1, 2, 4, 8, 16, and 32 for 0–25%, 26–50%, 51–75%, 76–90%, 91–99%, and 100%, respectively [ 15 ]. The Global Registry of Acute Coronary Event (GRACE) was widely used to risk stratification for ACS in acute phase [ 16 ]. For each AMI patient, GRACE score was calculated using online calculator on admission or within 24 h of admission ( http://www.outcomes-umassmed.org/grace ) by following variables: age, systolic blood pressure, heart rate, creatinine value, Killip class, cardiac arrest at admission, ST-segment deviation in ECG, and abnormal cardiac markers.…”
Section: Methodsmentioning
confidence: 99%
“…As the most frequently used risk assessment tools, the ‘Global Registry of Acute Coronary Events' (GRACE) and the ‘Can Rapid risk stratification of Unstable angina patients Suppress Adverse outcomes with Early implementation of the American College of Cardiology/American Heart Association guidelines' (CRUSADE) scores were recommended in describing the severity and mortality risk of AMI patients and management [ 19 ]. The average GRACE and CRUSADE scores were 124.5 and 21.74 in all AMI patients, respectively.…”
Section: Resultsmentioning
confidence: 99%